High PEEP levels are associated with overdistension and tidal recruitment/derecruitment in ARDS patients. Issue 9 (10th June 2015) - Retamal, J.; Bugedo, G.; Larsson, A.; Bruhn, A.
<x xml:space="preserve">Abstract</x> Background Positive end‐expiratory pressure (PEEP) improves gas exchange and respiratory mechanics, and it may decrease tissue injury and inflammation. The mechanisms of this protective effect are not fully elucidated. Our aim was to determine the intrinsic effects of moderate and higher levels of PEEP on tidal recruitment/derecruitment, hyperinflation, and lung mechanics, in patients with acute respiratory distress syndrome (ARDS). Methods Nine patients with ARDS of mainly pulmonary origin were ventilated sequential and randomly using two levels of PEEP: 9 and 15 cmH2O, and studied with dynamic computed tomography at a fix transversal lung region. Tidal recruitment/derecruitment and hyperinflation were determined as non‐aerated tissue and hyperinflated tissue variation between inspiration and expiration, expressed as percentage of total weight. We also assessed the maximal amount of non‐aerated and hyperinflated tissue weight. Results PEEP 15 cmH2O was associated with decrease in non‐aerated tissue in all the patients (P < 0.01). However, PEEP 15 cmH2O did not decrease tidal recruitment/derecruitment compared to PEEP 9 cmH2O (P = 1). In addition, PEEP 15 cmH2O markedly increased maximal hyperinflation (P < 0.01) and tidal hyperinflation (P < 0.05). Lung compliance decreased with PEEP 15 cmH2O (P < 0.001). Conclusion In this series of patients with ARDS of mainly pulmonary origin, application of high levels of PEEP did not decrease tidal recruitment/derecruitment, but instead consistently increased tidal and maximal hyperinflation.